2016
DOI: 10.1186/s12879-016-1704-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to outcome of bloodstream infections due to Candida parapsilosis complex

Abstract: BackgroundAlthough Candida albicans is the most common cause of fungal blood stream infections (BSIs), infections due to Candida species other than C. albicans are rising. Candida parapsilosis complex has emerged as an important fungal pathogen and became one of the main causes of fungemia in specific geographical areas. We analyzed the factors related to outcome of candidemia due to C. parapsilosis in a single tertiary referral hospital over a five-year period.MethodsA retrospective observational study of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 30 publications
0
29
2
3
Order By: Relevance
“…Overall 30‐days mortality for C parapsilosis was found to be lower compared to C albicans and C glabrata and compared to rarer species, nevertheless it was greater than in other experiences (23%‐27%) …”
Section: Discussionmentioning
confidence: 99%
“…Overall 30‐days mortality for C parapsilosis was found to be lower compared to C albicans and C glabrata and compared to rarer species, nevertheless it was greater than in other experiences (23%‐27%) …”
Section: Discussionmentioning
confidence: 99%
“…In recent years very few data have been available concerning the significantly enhanced trend for isolation of C. parapsilosis complex as a causative agent for candidaemia [24]. A recent observational study conducted in the centre of Italy showed that during the years 2010-2014, C. parapsilosis complex had a high incidence rate of isolation, and that the hospitalization in the ICU was independently associated with a significantly higher risk of mortality [7]. Unfortunately, no data are available concerning the relative risk of mortality associated with candidaemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the species distribution and the susceptibility profiles detected in the various hospitals evidenced discrepancies at the local level, with peculiarities among the hospitalization wards [5]. Indeed, patients hospitalized in intensive care units (ICUs) are generally considered to be at high risk of developing candidaemia, even though a generally increased incidence has been observed in other hospital wards [6,7]. Treatment of candidaemia mainly consists of the application of antifungal agents such as fluconazole, amphotericin B and, more recently, echinocandins.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of nosocomial infections caused by Candida has risen significantly in recent decades. Among this genus, C. parapsilosis is the species that has most notably increased in incidence, causing 10%‐25% of candidaemias in neonates and patients in intensive care units 5,17,24 . Candida parapsilosis infections are associated with the use of medical devices, such as central venous catheters, parenteral nutrition administration and healthcare worker contact 5,25‐28 .…”
Section: Discussionmentioning
confidence: 99%
“…External acquisition by medical devices is considered an important route of C. parapsilosis infection, and prolonged catheterisation has been demonstrated to be the most important underlying condition, with this factor being of greater relevance to the C. parapsilosis species complex than to C. albicans 2,5,16,17 . In 2015, Barbedo et al observed that the species identified in the catheter was not always responsible for the bloodstream infection, and different cryptic species of the C. parapsilosis complex could be identified in the same patient from both samples 18 …”
Section: Introductionmentioning
confidence: 99%